Dusted lines: a compilation of self-written poems / Nur’aliyah ‘Aqilah Safian and Irene Leong Yoke Chu - Safian, Nur’aliyah ‘Aqilah; Leong Yoke Chu, Irene (Academy of Language Studies, 2023)
Poetry is the art of words, where it conveys the beauty and sometimes humour in life (Borges, 2002). It is a great way for young people to find their creativity and expand their vocabulary which helps them with self-expression and language. It is also a great tool to reflect one’s passion in life to express their unexplained emotions or experiences (Rolfs, 2021). With the innovations of technology at our finger tips, just about anybody can write and share their original poems through various social media platforms. Thus, the creation of digital poetry e-book, Dusted Lines was formed. Dusted Lines is seen as an anthology of the author’s poetic self-journey in her teenage years to her adulthood where her experiences and thoughts are written alongside creative illustrations in the e-book. Based on a pilot survey, e-books and poetry are still popular among the younger generation. This e-book is purchasable and downloadable by just directly messaging the author through Instagram to receive a downloadable link. After an initial launch of just two weeks, positive reviews were received which shows that poetry reading and writing has the potential to attract a vast number of young readers.